2022
DOI: 10.1186/s13731-022-00201-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of potential and effective entrepreneurial capabilities in adolescents: modeling youth entrepreneurship structure using structural equation modeling

Abstract: This article emphasizes entrepreneurial skills in adolescents, in order to determine the relationship between entrepreneurial skills (dependent variable) and the key factors for their development: personal, social, and educational (independent variables). It has an empirical‒analytical design which is explanatory in nature. After the design, validation, and application of the evaluation instrument, the estimation was carried out using Structural Equation Modeling (SEM). The results show great impact of potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…Although adolescents are likely to go through a period of maturation, these changes may nonetheless be slow, as other personality traits undergo only a 10 percent change in late adulthood. Another study focused on entrepreneurial skills in adolescents to determine the relationship between the dependent variable and key factors in their development: personal, social, and educational (independent variables; Campo-Ternera et al, 2022). The results showed that the great influence of potential entrepreneurial ability on effective entrepreneurial activity is determined by the direct influence of personal qualities and life skills, as well as family.…”
Section: Discussionmentioning
confidence: 99%
“…Although adolescents are likely to go through a period of maturation, these changes may nonetheless be slow, as other personality traits undergo only a 10 percent change in late adulthood. Another study focused on entrepreneurial skills in adolescents to determine the relationship between the dependent variable and key factors in their development: personal, social, and educational (independent variables; Campo-Ternera et al, 2022). The results showed that the great influence of potential entrepreneurial ability on effective entrepreneurial activity is determined by the direct influence of personal qualities and life skills, as well as family.…”
Section: Discussionmentioning
confidence: 99%
“…(49) Campo-Ternera (2022) [127]: The paper studies the relationship between entrepreneurial capacity and key factors for the development of entrepreneurial skills such as social, personal, and educational. The results show that potential entrepreneurial capacity has an impact on effective entrepreneurial capacity, influenced by personal traits and life skills.…”
Section: Entrepreneurial Capacitymentioning
confidence: 99%
“…ISN 2707-2207 / ISSN 2707-2215 (en línea), julio-agosto, 2022, Volumen 6, Número 4 p 3698 (Sofian et al, 2022). El emprendimiento potencial tiene efecto positivo sobre el emprendimiento efectivo en el proceso educativo en donde están inmersos los adolescentes a las que se suma el ambiente familiar, por lo tanto, los factores personales y habilidades son una capacidad para el emprendimiento para los adolescentes, (Campo-Ternera et al, 2022). Un hogar tiene la capacidad y las herramientas innovadores para hacer frente diversas crisis que nos toca atravesar, con él se evidencia el alto potencial para emprender un negocio, (Sakka et al, 2022).…”
Section: Escuela De Innovación Socialunclassified